To solve the equation, we add 9 to both sides:
-3x - 9 + 9 = -21 + 9
This simplifies to:
-3x = -12
Next, we divide both sides by -3 to solve for x:
x = -12 / -3
This simplifies to:
x = 4
The equation −3x−9=−21 is solved as follows. Supply the correct numbers to complete the solution.(1 point)
−3x−9=−21
−3x= blank Add 9 to both sides.
x= blank Divide both sides by −3.
11 answers
The equation 10x+13=−12 is solved as follows. Supply the correct numbers to complete the solution.(1 point)
10x+13=−12
10x= blank Subtract 13 from both sides.
x= blank Divide both sides by 10.
10x+13=−12
10x= blank Subtract 13 from both sides.
x= blank Divide both sides by 10.
To solve the equation, we subtract 13 from both sides:
10x + 13 - 13 = -12 - 13
This simplifies to:
10x = -25
Next, we divide both sides by 10 to solve for x:
x = -25 / 10
This simplifies to:
x = -2.5
10x + 13 - 13 = -12 - 13
This simplifies to:
10x = -25
Next, we divide both sides by 10 to solve for x:
x = -25 / 10
This simplifies to:
x = -2.5
Solve 5−6x=−7 .(1 point)
x= blank
x= blank
To solve the equation, we isolate the variable x by subtracting 5 from both sides:
5 - 5 - 6x = -7 - 5
This simplifies to:
-6x = -12
Next, we divide both sides by -6 to solve for x:
x = -12 / -6
This simplifies to:
x = 2
5 - 5 - 6x = -7 - 5
This simplifies to:
-6x = -12
Next, we divide both sides by -6 to solve for x:
x = -12 / -6
This simplifies to:
x = 2
The equation 5/3x+11/3=−4/3 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
5/3x+11/3=−4/3
5/3x=
Subtract 11/3 from both sides.
x=
Multiply both sides by 3/5, the reciprocal of 5/3.
5/3x+11/3=−4/3
5/3x=
Subtract 11/3 from both sides.
x=
Multiply both sides by 3/5, the reciprocal of 5/3.
To solve the equation, we begin by subtracting 11/3 from both sides:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Next, we can simplify the equation further by simplifying the fractions:
5/3x = -5
To solve for x, we need to multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3x) = (3/5)(-5)
This simplifies to:
x = -3/5
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Next, we can simplify the equation further by simplifying the fractions:
5/3x = -5
To solve for x, we need to multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3x) = (3/5)(-5)
This simplifies to:
x = -3/5
The equation 5/3x+11/3=−4/3 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
5/3x+11/3=−4/3
5/3x= blank Subtract 11/3 from both sides.
x= blank Multiply both sides by 3/5, the reciprocal of 5/3.
5/3x+11/3=−4/3
5/3x= blank Subtract 11/3 from both sides.
x= blank Multiply both sides by 3/5, the reciprocal of 5/3.
To solve the equation, we begin by subtracting 11/3 from both sides:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Next, we can simplify the equation further by simplifying the fractions:
5/3x = -5
To solve for x, we need to multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3x) = (3/5)(-5)
This simplifies to:
x = -3/5
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Next, we can simplify the equation further by simplifying the fractions:
5/3x = -5
To solve for x, we need to multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3x) = (3/5)(-5)
This simplifies to:
x = -3/5
The equation 0.24x−0.74=−1.1 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
0.24x−0.74=−1.1
0.24x= blank Add 0.74 to both sides.
x= blank Divide both sides by 0.24.
0.24x−0.74=−1.1
0.24x= blank Add 0.74 to both sides.
x= blank Divide both sides by 0.24.
To solve the equation, we add 0.74 to both sides:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
This simplifies to:
0.24x = -0.36
Next, we divide both sides by 0.24 to solve for x:
x = -0.36 / 0.24
This simplifies to:
x = -1.5
0.24x - 0.74 + 0.74 = -1.1 + 0.74
This simplifies to:
0.24x = -0.36
Next, we divide both sides by 0.24 to solve for x:
x = -0.36 / 0.24
This simplifies to:
x = -1.5